2023
DOI: 10.2460/javma.23.02.0126
|View full text |Cite
|
Sign up to set email alerts
|

Overall good agreement of smartphone-based and standard base-apex electrocardiography in healthy sheep

Abstract: OBJECTIVE To assess and compare the quality of smartphone ECG tracings to standard (base-apex) ECG tracings and assess agreement of ECG parameters between smartphone-based ECG and standard ECG. ANIMALS 25 rams. PROCEDURES The rams were consecutively examined with standard ECG and smartphone-based ECG (KardiaMobile; AliveCor Inc) after physical examination. ECGs were compared for quality score, heart rate, and ECG waves, complexes, and intervals. Quality scores were based on the presence or absence of basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
2
5
2
Order By: Relevance
“…This nding may be attributed to inherent di culty in maintaining optimal contact of electrodes with skin when using the smartphone-based device compared to the digital telemetric ECG device. However, the device allowed identi cation of normal sinus rhythm in all foals, and, in contrast to ndings from previous studies in sheep and goats (Smith 2020; King et al 2023), our results show a substantial agreement between rECG and sECG tracing quality.…”
Section: Discussioncontrasting
confidence: 99%
“…This nding may be attributed to inherent di culty in maintaining optimal contact of electrodes with skin when using the smartphone-based device compared to the digital telemetric ECG device. However, the device allowed identi cation of normal sinus rhythm in all foals, and, in contrast to ndings from previous studies in sheep and goats (Smith 2020; King et al 2023), our results show a substantial agreement between rECG and sECG tracing quality.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, consistent with studies in small ruminants (Smith 2020 ; King et al 2023 ), the quality of sECG traces was found to be lower than those of rECG traces. This finding may be attributed to inherent difficulty in maintaining optimal contact of electrodes with skin when using the smartphone-based device compared to the digital telemetric ECG device.…”
Section: Discussionsupporting
confidence: 89%
“…The differences may be related to a certain restlessness of foals when handled as compared to adult animals. In a study assessing feasibility of smartphone-based ECG recording in sheep, a lower percentage of interpretability was found (65%) (King et al 2023 ), reasonably because of the feral temperament of the animals enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations